Viajantes Radicais, pelo caminho de Levi Strauss. - Lago, Jader (Brazil; Canal Azul and ESPN Brazil, 2010)
From 1935 to 1939 Claude Levi-Strauss traveled to Brazil to understand the human soul through the fascinating indigenous communities of Kadiwéu, Bororo, Nambikwara and Tupi-Kawahib. They are tribes with different religions, culture and history, but currently with the same problem: the increasing deforestation and cattle raising has altered their lives and threatening their existence. The film features NGO representatives, scholars and activists who talk about the role of the indigenous territories in preserving the rain-forests.
Verzio Film Festival Submission
Keywords: Documentary films